The largest western experience on salvage hepatectomy for recurrent hepatocellular carcinoma: propensity score-matched analysis on behalf of He.RC.O.Le.Study Group. Issue 8 (August 2022) - Iaria, Maurizio; Bianchi, Giorgio; Fazio, Federico; Ardito, Francesco; Perri, Pasquale; Pontarolo, Nicholas; Conci, Simone; Donadon, Matteo; Zanello, Matteo; Lai, Quirino; Famularo, Simone; Molfino, Sarah; et al.
Abstract: Background: We aimed to evaluate, in a large Western cohort, perioperative and long-term oncological outcomes of salvage hepatectomy (SH) for recurrent hepatocellular carcinoma (rHCC) after primary hepatectomy (PH) or locoregional treatments. Methods: Data were collected from the Hepatocarcinoma Recurrence on the Liver Study Group (He.RC.O.Le.S.) Italian Registry. After 1:1 propensity score-matched analysis (PSM), two groups were compared: the PH group (patients submitted to resection for a first HCC) and the SH group (patients resected for intrahepatic rHCC after previous HCC-related treatments). Results: 2689 patients were enrolled. PH included 2339 patients, SH 350. After PSM, 263 patients were selected in each group with major resected nodule median size, intraoperative blood loss and minimally invasive approach significantly lower in the SH group. Long-term outcomes were compared, with no difference in OS and DFS. Univariate and multivariate analyses revealed only microvascular invasion as an independent prognostic factor for OS. Conclusion: SH proved to be equivalent to PH in terms of safety, feasibility and long-term outcomes, consistent with data gathered from East Asia. In the awaiting of reliable treatment-allocating algorithms for rHCC, SH appears to be a suitable alternative in patients fit for surgery, regardless of the previous therapeutic modality implemented.